#MeToo? Legal Discourse and Everyday Responses to Sexual Violence - Alison Gash; Ryan Harding (Laws, 2018)
Legal consciousness scholars identify the ways in which law is referenced to authorize, define and evaluate behaviors and choices that occur far outside any formal legal framework. They define legality as the “meanings, sources of authority, and cultural practices that are commonly recognized as legal, regardless of who employs them or for what ends.” We use the idea of legality to argue that, in matters of sexual assault and rape, the limits of the law extend beyond the courtroom. Rather than simply influencing or guiding only those who are willing to consult the law in their efforts to seek justice, laws and legal discourse have the potential to frame and constrain any attempt to discuss experiences of sexual violence. #MeToo and other forms of “consciousness-raising” for sexual violence highlight the limiting effects of law and legal discourse on public discussion of sexual violence. We find that, paradoxically, in the case of sexual violence law has the capacity to undermine the goals and benefits of consciousness-raising approaches, privatizing the experience of sexual assault and silencing its victims.